Evaluation of the Effect of Local Water Chemistry on Trace Metal Accumulation in Puget Sound Shellfish Shows That Concentration Varies With Species, Size, and Location - Bates, Eileen H.; Alma, Lindsay; Ugrai, Tamas; Gagnon, Alexander; Maher, Michael; McElhany, Paul; Padilla-Gamiño, Jacqueline L. (Frontiers in Marine Science, 2021)
Global climate change is causing ocean acidification (OA), warming, and decreased dissolved oxygen (DO) in coastal areas, which can cause physiological stress and compromise the health of marine organisms. While there is increased focus on how these stressors will affect marine species, there is little known regarding how changes in water chemistry will impact the bioaccumulation of trace metals. This study compared trace metal concentrations in tissue of mussels (Mytilus galloprovincialis) and Olympia oysters (Ostrea lurida) in Puget Sound, Washington, a region that experiences naturally low pH, seasonal hypoxia, and is surrounded by urbanized and industrialized areas. Shellfish were held at three sites (Carr Inlet, Point Wells, and Dabob Bay) where oceanographic data was continuously collected using mooring buoys. Using inductively coupled plasma mass-spectrometry (ICP-MS) to measure trace metals in the tissue, we found differences in accumulation of trace metals based on species, location, and shellfish size. Our study found differences between sites in both the mean metal concentrations and variability around the mean of those concentrations in bivalves. However, high metal concentrations in bivalves were not associated with high concentrations of metals in seawater. Metal concentrations in shellfish were associated with size: smaller shellfish had higher concentrations of metals. Carr Inlet at 20 m depth had the smallest shellfish and the highest metal concentrations. While we could not eliminate possible confounding factors, we also found higher metal concentrations in shellfish associated with lower pH, lower temperature, and lower dissolved oxygen (conditions seen at Carr Inlet at 20 m and to a lesser extent at Point Wells at 5 m depth). There were also significant differences in accumulation of metals between oysters and mussels, most notably copper and zinc, which were found in higher concentrations in oysters. These findings increase our understanding of spatial differences in trace metal bioaccumulation in shellfish from Puget Sound. Our results can help inform the Puget Sound aquaculture industry how shellfish may be impacted at different sites as climate change progresses and coastal pollution increases.